Proceso atención de enfermería en paciente de 31 años con tuberculosis miliar. - Vera Moreira, Gianella Alejandra (2022)
Miliary Tuberculosis is the most feared form of Tuberculosis that spreads throughout the bloodstream, as it progresses it affects multiple organs until causing the death of the person, through our nursing care we provide emotional support to the patient and family to cope how hard and irreversible the treatment and the consequences are. The present clinical case is about a 31-year-old female patient who was admitted to the emergency area of the Hospital Sagrado Corazón de Jesús de Quevedo, due to presenting a clinical picture of more or less 3 weeks of evolution characterized by odynophagia, fever, vomiting and chills for several days before admission, respiratory distress, dry cough, and hyporexia, during his assessment and diagnosis the presence of Miliary Tuberculosis with a history of positive HIV was determined. The nursing care process is considered a systematic, scientific, logical, rational and organized method that allows us to provide efficient and individualized humanistic care in order to achieve results and improve the quality of life of our patients. Through this process of Nursing Care (PAE) the patient with Miliary Tuberculosis is assessed and a critical analysis is reached through the cephalo-caudal assessment and the use of Marjory Gordon's functional patterns that are very useful to reach to our nursing diagnosis and carry out the different nursing interventions according to the needs of the patient.